A Teenage Girl with Acute Dyspnea and Hypoxemia during Red Blood Cell Transfusion - U. Pandee; P. Tanpowpong; P. Thongpo (Case Reports in Pediatrics)
Transfusion-related acute lung injury (TRALI) can cause morbidity and mortality. We present the case of teenager who developed dyspnea and hypoxemia few hours after red cell transfusion. After being admitted for close monitoring and oxygen therapy, her symptoms spontaneously resolved. Message: dyspnea during red cell transfusion should raise the suspicion of TRALI.